3D hierarchical biobased gel electrolyte with superior ionic conductivity and flame resistance for suppressing lithium dendrites via alloying and sieving mechanisms. (1st February 2022) - Huang, Yangze; Wang, Yongqin; Fu, Yu
Abstract: The unmanageable growth of lithium dendrites has severely restrained the application of Li mental anode for higher energy density batteries. To tackle the issue of lithium dendrites, a novel dual strategy of "dead lithium" dissipation via the lithium alloying and sieving effect were developed to endow a biobased gel polymer electrolyte (GPE) with excellent performance in effectively suppressing the growth of lithium dendrite at high current density. Specifically, based on the electrospun cellulose acetate/poly (lactic acid)/black phosphorus-bismuth sulfide (PCA/Bi2 S3 -BP) membranes, 3D-hierarchical structure with numerous polar functional groups was applied to improve the electrochemical efficiency and mechanical flexibility of biobased gel electrolytes. The dual mechanisms of alloying reactions and sieving effect from Bi2 S3 and BP was for the first time applied to disrupt dendrite growth from the bottom-up. Furthermore, the puckered "honeycomb" structure of BP nanosheets provided a specific mass route for directional Li + transmission and could immobilize PF6- for the Li-ion transference number improvement. The as-prepared GPE presented a superior lithium ionic conductivity of 8.37 × 10 −3  S cm −1, together with prominent lithium ion transference up to 0.64 at 25 °C. The assembled Li/GPE/NCM523 batteries by PCA/Bi2 S3 -BP gel polymer electrolyte displayed initial discharge capacity of 141.68 mAh g −1 with capacity retention of 90.23% after 200 cycles at 1C. Therefore, PCA/Bi2 S3 -BP GPE with green skeleton materials demonstrated its promising application in high electrochemical performance and safety Li mental batteries.